Molecular Diagnostics of Banana Fusarium Wilt Targeting Secreted-in-Xylem Genes - Carvalhais, Lilia C.; Henderson, Juliane; Rincon-Florez, Vivian A.; O’Dwyer, Cecilia; Czislowski, Elizabeth; Aitken, Elizabeth A. B.; Drenth, André (Frontiers in Plant Science, 2019)
Fusarium wilt is currently spreading in banana growing regions around the world leading to substantial losses. The disease is caused by the fungus Fusarium oxysporum f. sp. cubense (Foc), which is further classified into distinct races according to the banana varieties that they infect. Cavendish banana is resistant to Foc race 1, to which the popular Gros Michel variety succumbed last century. Cavendish effectively saved the banana industry, and became the most cultivated commercial variety worldwide. However, Foc tropical race 4 (TR4) subsequently emerged in Southeast Asia, causing significant yield losses due to its high level of aggressiveness to Cavendish and other commonly grown varieties. Preventing further spread is crucially important in the absence of effective control methods or resistant market-acceptable banana varieties. Implementation of quarantine and containment measures depends on early detection of the pathogen through reliable diagnostics. In this study, we tested the hypothesis that secreted in xylem (SIX) genes, which currently comprise the only known family of effectors in F. oxysporum, contain polymorphisms to allow the design of molecular diagnostic assays that distinguish races and relevant VCGs of Foc. We present specific and reproducible diagnostic assays based on conventional PCR targeting SIX genes, using as templates DNA extracted from pure Foc cultures. Sets of primers specifically amplify regions of: SIX6 in Foc race 1, SIX1 gene in TR4, SIX8 in subtropical race 4, SIX9/SIX10 in Foc VCG 0121, and SIX13 in Foc VCG 0122. These assays include simplex and duplex PCRs, with additional restriction digestion steps applied to amplification products of genes SIX1 and SIX13. Assay validations were conducted to a high international standard including the use of 250 Fusarium spp. isolates representing 16 distinct Fusarium species, 59 isolates of F. oxysporum, and 21 different vegetative compatibility groups (VCGs). Tested parameters included inter and intraspecific analytical specificity, sensitivity, robustness, repeatability and reproducibility. The resulting suite of assays is able to reliably and accurately detect R1, STR4, TR4 as well as two VCGs (0121 and 0122) causing Fusarium wilt in bananas.